Photophysiological responses of Southern Ocean phytoplankton to changes in CO 2 concentrations: Short-term versus acclimation effects - Trimborn, S; Thoms, S; Petrou, K; Kranz, SA; Rost, B (2014)
The present study examines how different pCO2 acclimations affect the CO2- and light-dependence of photophysiological processes and O2 fluxes in four Southern Ocean (SO) key phytoplankton species. We grew Chaetoceros debilis (Cleve), Pseudo-nitzschia subcurvata (Hasle), Fragilariopsis kerguelensis (O'Meara) and Phaeocystis antarctica (Karsten) under low (160μatm) and high (1000μatm) pCO2. The CO2- and light-dependence of fluorescence parameters of photosystem II (PSII) were determined by means of a fluorescence induction relaxation system (FIRe). In all tested species, nonphotochemical quenching (NPQ) is the primary photoprotection strategy in response to short-term exposure to high light or low CO2 concentrations. In C. debilis and P. subcurvata, PSII connectivity (p) and functional absorption cross-sections of PSII in ambient light (σPSII') also contributed to photoprotection while changes in re-oxidation times of Qa acceptor (τQa) were more significant in F. kerguelensis. The latter was also the only species being responsive to high acclimation pCO2, as these cells had enhanced relative electron transport rates (rETRs) and σPSII' while τQa and p were reduced under short-term exposure to high irradiance. Low CO2-acclimated cells of F. kerguelensis and all pCO2 acclimations of C. debilis and P. subcurvata showed dynamic photoinhibition with increasing irradiance. To test for the role and presence of the Mehler reaction in C. debilis and P. subcurvata, the light-dependence of O2 fluxes was estimated using membrane inlet mass spectrometry (MIMS). Our results show that the Mehler reaction is absent in both species under the tested conditions. We also observed that dark respiration was strongly reduced under high pCO2 in C. debilis while it remained unaltered in P. subcurvata. Our study revealed species-specific differences in the photophysiological responses to pCO2, both on the acclimation as well as the short-term level. © 2013 The Authors.